Application of passive sorbent tube and canister samplers for volatile organic compounds at refinery fenceline locations in Whiting, Indiana. (1st February 2018) - Mukerjee, Shaibal; Smith, Luther A.; Caudill, Motria P.; Oliver, Karen D.; Whipple, Wayne; Whitaker, Donald A.; Cousett, Tamira A.
ABSTRACT: Select volatile organic compounds (VOCs) in ambient air were measured at four fenceline sites at a petroleum refinery in Whiting, IN, using modified EPA Method 325 A/B with passive tubes and EPA Compendium Method TO-15 with canister samplers. One-week, time-integrated samplers were deployed for 8 weeks with tubes and canister samplers deployed in duplicate. Good precision was obtained from the duplicate tubes (<7%) and duplicate canisters (≤10%) for BTEX, perchloroethylene, and styrene. The tubes yielded statistically significantly higher concentrations than canisters for benzene, toluene, ethylbenzene, and m, p -xylene. However, all differences were estimated to be <0.1 ppbv. No concentration differences among the four Whiting sites were found for any of the VOCs. Implications : Recently enacted EPA Methods 325A/B use passive-diffusive tube samplers to measure benzene at refinery fenceline locations. This pilot study presents VOC data applying a modified version of EPA Method 325 A/B and its comparison to EPA Compendium Method TO-15 canister samplers at four refinery fenceline sites. The findings from this study provide additional confidence in application of the tube method at refineries to ascertain VOC source influence since tube and canister samplers were comparable and good precision was obtained from duplicate sampling for both methods. No overall difference in these reported VOC concentrations was found between Whiting sites for tubes or canisters.